2022
DOI: 10.3390/microorganisms10040766
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Communities of Forest Soils along Different Elevations: Diversity, Structure, and Functional Composition with Potential Impacts on CO2 Emission

Abstract: Soil bacteria are important components of forest ecosystems, there compostion structure and functions are sensitive to environmental conditions along elevation gradients. Using 16S rRNA gene amplicon sequencing followed by FAPROTAX function prediction, we examined the diversity, composition, and functional potentials of soil bacterial communities at three sites at elevations of 1400 m, 1600 m, and 2200 m in a temperate forest. We showed that microbial taxonomic composition did not change with elevation (p = 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 52 publications
1
4
0
Order By: Relevance
“…The soil microorganisms also play an important role in plant litter degradation, thereby inducing changes in soil physical and chemical properties. 22,23 Specific exergy of the marine species reported by Semerciöz et al 14 was between 40 kJ/g when n = 1 and 1.48 Â 10 À3 when n = 5; in the present paper specific exergy of the sap consumed in step 1 was 1268 kJ/77 g = 66 kJ/g, in step n = 5 specific exergy become 4.68 Â 10 À2 . In the present paper, if the starting exergy specific exergy of the sap would have been 40 kJ/ g, specific exergy value attained in step n = 5 would be 2.83 Â 10 À2 , for example, 9% different than the number presented by Semerciöz et al 14 Exergy efficiency values reported by Semerciöz et al 14 were between 7.8 Â 10 À2 and 3.7 Â 10 À5 , while in the present paper, it is constant as 7.8 Â 10 À2 .…”
Section: Discussionsupporting
confidence: 43%
See 1 more Smart Citation
“…The soil microorganisms also play an important role in plant litter degradation, thereby inducing changes in soil physical and chemical properties. 22,23 Specific exergy of the marine species reported by Semerciöz et al 14 was between 40 kJ/g when n = 1 and 1.48 Â 10 À3 when n = 5; in the present paper specific exergy of the sap consumed in step 1 was 1268 kJ/77 g = 66 kJ/g, in step n = 5 specific exergy become 4.68 Â 10 À2 . In the present paper, if the starting exergy specific exergy of the sap would have been 40 kJ/ g, specific exergy value attained in step n = 5 would be 2.83 Â 10 À2 , for example, 9% different than the number presented by Semerciöz et al 14 Exergy efficiency values reported by Semerciöz et al 14 were between 7.8 Â 10 À2 and 3.7 Â 10 À5 , while in the present paper, it is constant as 7.8 Â 10 À2 .…”
Section: Discussionsupporting
confidence: 43%
“…In addition to helping the plants to accumulate nitrogen, phosphorus, and sulfur in the soil, microorganisms accelerate nutrient cycling through organic matter decomposition and nitrogen‐fixing. The soil microorganisms also play an important role in plant litter degradation, thereby inducing changes in soil physical and chemical properties 22,23 …”
Section: Discussionmentioning
confidence: 99%
“…Linking the variation of microbial communities to ecosystem functionality is a key challenge and the J o u r n a l P r e -p r o o f Journal Pre-proof ultimate goal in microbial ecology (Yan et al, 2020;Sun et al, 2022). While numerous studies have explored changes in bacterial communities, little research has focused on the resulting changes in ecological functions (Wang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Research on these functional groups can provide valuable insights into the mechanisms underlying bacterial-mediated soil processes (Jiang et al, 2021). Recently, databases such as Functional Annotation of Prokaryotic Taxa (FAPROTAX), BugBase, and Tax4Fun, have been used to identify potential bacterial functions based on 16S rRNA gene sequencing (Li et al, 2019a;Jiang et al, 2021;Sun et al, 2022). Of these, FAPROTAX is particularly useful for monitoring soil ecology in agro-ecosystems, as it can annotate a series of functional bacteria, including those related to soil C, N nutrients cycling, predatory/exoparasitic and soil-borne pathogenic bacteria (Zhao et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…To increase forest cover and reduce the negative impacts of climate change on a global scale [1], both natural regeneration and silvicultural assumptions need to be implemented by growing forests on low-value land (including post-industrial land) and post-agricultural land exhausted by long-term use [2]. The long-term use of soils in agriculture (restricted crop rotation or monocultures) leads to their gradual degradation, especially in terms of biodiversity.…”
Section: Introductionmentioning
confidence: 99%